Review of recent progress in the study of corrosion products of steels in a hydrogen sulphide environment. (15th July 2018) - Wen, Xiangli; Bai, Pengpeng; Luo, Bingwei; Zheng, Shuqi; Chen, Changfeng
Highlights: Recent progress in the study of corrosion products in a H2 S environment is reviewed. Corrosion behaviour of carbon steel in a wet H2 S environment is summarized. Polymorphous Fe-S compounds are the corrosion products of steel in H2 S environments. The phase transition follows: mackinawite  →  cubic FeS  →  troilite  →  pyrrhotite  →  pyrite. The phase changes of the corrosion product greatly affect the corrosion behaviour of the steel. Abstract: In this paper, recent research progress regarding carbon steel corrosion products and their effects on the subsequent corrosion process in H2 S environments is reviewed. The classification of corrosion products; their dependence on the initiation, growth, and transformation processes; and the corrosion behaviour of carbon steels under wet H2 S environments, and the subsequent corrosion products, are summarized and reviewed. In addition, the basic theory regarding the development of corrosion product films and the relationship between the corrosion products and hydrogen diffusion are discussed. Finally, future research and development directions of this field are proposed.